5x+y=24---1

-5x-4y=-56---2

X=?

Y=?

Adding equation 1 & 2

(5x+y)+(-5x-4y)=24+(-56)

-3y=-32

\(\displaystyle{Y}=\frac{{32}}{{3}}\)

Substitute the value of y in 1st eq

5x+y=24

\(\displaystyle{5}{x}+{\left(\frac{{32}}{{3}}\right)}={24}\)

\(\displaystyle{5}{x}={24}-\frac{{32}}{{3}}=\frac{{40}}{{3}}\)

\(\displaystyle{X}=\frac{{8}}{{3}}\)

-5x-4y=-56---2

X=?

Y=?

Adding equation 1 & 2

(5x+y)+(-5x-4y)=24+(-56)

-3y=-32

\(\displaystyle{Y}=\frac{{32}}{{3}}\)

Substitute the value of y in 1st eq

5x+y=24

\(\displaystyle{5}{x}+{\left(\frac{{32}}{{3}}\right)}={24}\)

\(\displaystyle{5}{x}={24}-\frac{{32}}{{3}}=\frac{{40}}{{3}}\)

\(\displaystyle{X}=\frac{{8}}{{3}}\)